The development of a measure of work-related underload - Naude, Megan N., author; Fisher, Gwenith, advisor; Byrne, Zinta, committee member; Steger, Michael, committee member; Henle, Chris, committee member (Colorado State University. Libraries, 2015)
This study outlines the development of the construct of work-related underload as well as a scale to measure underload. Underload has been given limited attention in the stress literature but could be a significant source of stress and other negative outcomes in the workplace. After reviewing the literature and the theoretical background related to underload, a clear definition of underload was established based on employees' perceptions, expectations, and desires related to workload. This definition informed the development of a three-factor scale to measure underload. Data from two development samples was collected in order to evaluate the reliability and validity of the scale. The results provide evidence of the internal consistency and construct validity of the three-dimensional scale. The work-related underload scale may be used in the future to explore the antecedents and consequences associated with the experience of underload at work.
Keywords: underload